Social impact and social return on investment of the potential development project for elderly care service in Mae Mok subdistrict, Thoen district, Lampang province - Atsalikorn, Watsana; Laothamatas, Jiraporn; Prasoptham, Jira (Kasetsart Journal of Social Sciences, 2023)
This research study aimed to assess social impact and social return on investment of the potential development project for elderly care service, community enterprise of the exemplary community: Mae Mok subdistrict, Thoen district, Lampang province. This research was qualitative with a mixed data-collection methodology containing documentary research, focus group, and in-depth interview with the project’s founders and stakeholders. The analyses conducted the social impact assessment (SIA) and social return on investment (SROI) using the theory of change, impact value chain, indicators, deadweight, attribution, drop-off, and financial proxy. The four essential informants of this research study were: (1) elderly caregivers; (2) elderly caregivers’ families; (3) clients; and (4) villagers (members of the community, Mae Mok subdistrict). The study results showed that the social impact included the community’s economic change - creating employment and raising incomes; social change—being more respected and feeling proud of becoming an elderly caregiver in one’s hometown, and environmental change—utilizing the community’s natural capital to benefit community’s members. The SROI ratio was 1:5.83, which indicates that every 1 baht of investment delivers 5.83 baht of social value back to all stakeholders.